Nutritional, physicochemical, and antioxidant characterization of pomegranate, beetroot, and carrot concentrates supplemented functional whey beverages - Muhammad Saleem; Zulfiqar Ahmad; Muhammad Waseem; Tawfiq Alsulami; Muhammad Rizwan Javed; Muhammad Farhan; Gulzar Ahmad Nayik; Muhammad Faisal Manzoor; Gholamreza Abdi (Food Chemistry: X)
The study aimed to investigate the nutritional, antioxidant, physicochemical, and sensorial properties of pomegranate concentrate (PC), beetroot concentrate (BC), and carrot concentrate (CC) and their supplemented whey beverages. Results revealed that PC exhibited the highest ash, Na, K, Ca, Mg, Fe, Zn, and ascorbic acid concentration than BC and CC. Also, the highest total phenolic contents (TPC), total flavonoid contents (TFC), 2, 2-Diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) were recorded in PC, while maximum β-carotene and anthocyanin were found in CC and PC. In the case of prepared functional beverages, the pomegranate concentrate-whey beverage (PCWb) exhibited the maximum ash, Na, K, Ca, Mg, Fe, Zn, and ascorbic acid contents that beetroot concentrate-whey beverage (BCWb) and carrot concentrate-whey beverage (CCWb). The highest TPC (27.3 mg GAE/100 mL), TFC (13.3 mg QE/100 mL), DPPH (41 %), and FRAP (101.3 μmol TE/100 mL) were found in PCWb than BCWb and CCWb. Sensory evaluation outcomes reported PCWb for better taste, color, and overall acceptability. Conclusively, the current study reported that PC is the best choice for value addition in ready-to-drink functional beverages, and future research is required to evaluate its storage stability and health-promoting activities.